The Effect of E-Infographic Media on Vocational High School Students’ Learning Outcomes in Hair Layering Technique Material - Dachi, Rosni artisan nita nauli (Universitas Negeri Semarang, 2025)
The advancement of information technology in the digital era opens opportunities for developing innovative learning media, including in vocational high schools (SMK). However, conventional methods such as lectures and limited media usage still dominate, resulting in low student participation and understanding. The hair layering technique material in the beauty program requires a visual approach. This study used a quantitative quasi-experimental method with a nonequivalent control group design to examine the effect of e-infographic media on the cognitive learning outcomes of 11th-grade students at SMK Negeri 6 Semarang. The analysis results showed no significant difference in the pretest (p=0.343), but a significant improvement in the posttest (p=0.011), proving that e-infographic media effectively enhances learning outcomes with engaging and easy-to-understand visualizations.